Beyond thirty: Treasury issuance of long-term bonds from 1953 to 1965 - Kenneth D. Garbade (Federal Reserve Bank of New York, 2017)
Ever since the emergence of regular and predictable issuance of coupon-bearing Treasury debt in the 1970s, thirty years has marked the outer boundary of Treasury bond maturities. However, longer-term bonds were not unknown in earlier years. Seven such bonds, including one with a forty-year term, were issued between 1955 and 1963. This paper examines the circumstances that led to the issuance of these seven bonds.
Keywords: H63; N22; 330; Treasury debt management; long-term bonds; U.S. Treasury